ddRAD-seq variant calling in peach and the effect of removing PCR duplicates - Ksouri, Najla; Benítez, M; Aballay, Maximiliano Martín; Sanchez, Gerardo; Contreras-Moreira, Bruno; Gogorcena Aoiz, Yolanda (ISHS, 2024)
X International Peach Symposium, Naoussa (Grecia), diciembre de 2022